Risk of prostatitis in patients with type 2 diabetes mellitus: An observational retrospective cohort study of canagliflozin versus other antihyperglycemic agents using propensity score matching - Zhong Yuan; Carolyn H. Jeffcoat; Saberi Rana Ali; Anthony G. Sena; Martijn J. Schuemie; Patrick B. Ryan; Sergio A. Fonseca (PLoS ONE, 2026)
Purpose Prostatitis has been reported in patients with type 2 diabetes mellitus (T2DM) receiving antihyperglycemic agents (AHAs). This study was conducted to evaluate the risk of prostatitis with canagliflozin in response to a specific Health Authority query. Methods This retrospective cohort study used data from adult male patients with T2DM who were new users of canagliflozin (target) or comparators (empagliflozin, dapagliflozin, sitagliptin, and liraglutide). Data were obtained from 8 global administrative claims databases, transformed to a Common Data Model for consistent analysis across databases. Pairwise comparisons were conducted using propensity scores to match canagliflozin users to users of each comparator at a 1:n ratio (maximum n = 100). Hazard ratios were estimated using a Cox proportional hazards model, conditioned on the matched set. Results A total of 388,893 adult male patients with T2DM received canagliflozin across databases (mean age, 51.2–71.7 years) and were matched to 657,134 patients receiving empagliflozin, 340,539 receiving dapagliflozin, 819,047 receiving sitagliptin, and 278,684 receiving liraglutide. On-treatment incidence rates showed that prostatitis was uncommon in the canagliflozin cohort in nearly all databases (4.2–7.7 per 1000 person-years) and were similar to those of the comparator treatments. The exception was a higher crude incidence rate in the Merative MarketScan ® Medicare Supplemental Database (10.1–12.1 per 1000 person-years). Propensity score matching achieved good balance in all available covariates, and effect estimates were relatively close to a hazard ratio of 1.0, varying on both sides of the null effect. Minimum detectable relative risks were low in most databases, and meta-analytic estimates were near 1.0, with all upper bounds <1.50. No association (either increased or decreased risk) was found with canagliflozin versus other AHAs. Conclusions This analysis found no evidence of a statistically significantly increased risk of prostatitis among adult male patients with T2DM receiving canagliflozin compared with the other AHAs evaluated in this study.